Zinc and/or Selenium Enriched Spirulina as Antioxidants in Growing Rabbit Diets to Alleviate the Deleterious Impacts of Heat Stress during Summer Season - Fawzia Hassan; Samia Mobarez; Manal Mohamed; Youssef Attia; Aml Mekawy; Khalid Mahrose (Animals, 2021)
Effects of dietary supplemental zinc and/ or selenium enriched spirulina (Zn-Sp, Se-Sp and Zn-Se-Sp, respectively) as antioxidants on growth performance, nutrient digestibility, plasma biochemicals and antioxidant status of growing rabbits under summer conditions were evaluated. A total of 160 New Zealand White male rabbits at six-weeks-old were randomly assigned to four groups. The first group received untreated diet (control). The other groups received diet supplemented with 100 mg Zn-Sp/kg diet, 0.5 mg Se-Sp/kg diet or 100 mg Zn-Sp+ 0.5 mg Se-Sp, respectively. The findings showed that the supplemented diets enhanced growth performance of rabbits at marketing. Rabbits fed Zn-Sp exhibited high dry and organic matter digestibilities while those fed Zn-Sp and Zn-Se-Sp diet supplemented achieved high crude protein digestibility. Rabbits fed diet supplemented with Zn-Se-Sp gave the highest hot carcass weight when competed with their counterparts. Zn-Sp and Zn-Se-Sp supplemented diets tended to promote dressing percentage. Low concentrations of plasma total cholesterol, LDL-cholesterol and VLDL-cholesterol were recorded by Se-Sp and Zn-Se-Sp groups. Rabbits fed Se-Sp, Zn-Se-Sp had the greatest HDL, plasma TAC and catalase and the lowest TBARs. Conclusively, dietary supplementation of 100 mg Zn-Sp, 0.5 mg Se-Sp or their combination could improve growth performance, nutrients digestibility and antioxidant status of heat stressed growing rabbits.